Iatrogenic immune-mediated neuropathies: diagnostic, epidemiological and mechanistic uncertainties for causality and implications for clinical practice. Issue 9 (8th June 2021) - Goedee, H Stephan; Attarian, Shahram; Kuntzer, Thierry; Van den Bergh, Peter; Rajabally, Yusuf A
Abstract : Acute and chronic immune-mediated neuropathies have been widely reported with medical intervention. Although causal relationship may be uncertain in many cases, a variety of drugs, several vaccination types, surgical procedures and bone marrow transplants have been reported as possible cause or trigger of a putative immune-mediated response resulting in acute and chronic neuropathies. We conducted a systematic review of the literature from 1966 to 2020 on reported cases of possible iatrogenic immune-mediated neuropathies. We determined in each case the likelihood of causality based on frequency of the association, focusing primarily on clinical presentation and disease course as well as available ancillary investigations (electrophysiology, blood and cerebrospinal fluid and neuropathology). The response to immunotherapy and issue of re-exposure were also evaluated. We also considered hypothesised mechanisms of onset of immune-mediated neuropathy in the specific iatrogenic context. We believe that a likely causal relationship exists for only few drugs, mainly antitumour necrosis factor alpha agents and immune checkpoint inhibitors, but remains largely unsubstantiated for most other suggested iatrogenic causes. Unfortunately, given the lack of an accurate diagnostic biomarker for most immune-mediated neuropathies, clinical assessment will often override ancillary investigations, resulting in lower levels of certainty that may continue to cast serious doubts on reliability of their diagnosis. Consequently, future reports of suspected cases should collect and exhaustively assess all relevant data. At the current time, besides lack of evidence for causality, the practical implications on management of suspected cases is extremely limited and therapeutic decisions appear likely no different to those made in non-iatrogenic cases.